ANALYSIS OF THE POTENTIAL RETRIBUTION OF TOURISM LOCATIONS IN THE CITY OF BANDA ACEH - Hamdani (Lembaga Riset dan Inovasi Kreyat Center, 2023)
Issues raised in this thesis is the analysis of potential retribution tourism locations in Banda Aceh. The purpose of this study was to determine the levy to identify potential locations in Banda Aceh tourism and how big the potential contribution of tourism levy locations in Banda Aceh Banda Aceh to PAD. The analytical method used in this research is descriptive method whose aim is to shortly describe or depict phenomena or relations among the phenomena studied with a systematic, factual and accurate. Data obtained in this research is secondary data. The analysis showed levy Potential attractions in Banda Aceh from 2011 to 2015 increased by different percentages in each year. Of 26 attractions in Banda Aceh new 8 attractions which collected the fees or by 31%, while as many as 18 attractions more or 69% has not levied the fees and have not yet developed well and Contributions levy attractions for the year 2011 to the year 2015 in Banda Aceh is still low and its effect on local revenue (PAD).